The Role of The Humanist Approach to Inter-Korean Diplomatic Relations During the DPRK’s Nuclear Crisis - Sopia, Siti; Djumala, Darmansjah; Sudirman, Arfin (Yayasan Ilomata, 2025)
Relations between inter-Korean have worsened as tensions from the DPRK nuclear crisis have continued to escalate. Amidst the existing tensions, some of the Republic of Korea regimes have taken a humanist approach in dealing with the DPRK, which has resulted in improving relations between both countries. The author uses Samuel P. Huntington's political order theory to explore a stable and effective political system in managing conflict and making decisions. This study uses qualitative methods with secondary sources from journals, books, reports, official documents, and official websites. The results of this study indicate that the humanist approach is more effective in dealing with the DPRK through meetings held by the leaders of the two countries to build cooperative relations such as the construction of the Kaesong Industrial Complex, economic aid worth hundreds of billions of Won to prevent North Korea's nuclear development, and dialogue conducted through state meetings. In addition, policies made by the Republic of Korea, such as the Sunshine Policy, are able to embrace the DPRK and prioritize dialogue when the DPRK violates the agreement in cooperation without unilaterally terminating the cooperative relationship as was done by the Lee Myung-bak and Park Geun-hye regimes with their conservative approaches. Political institutions also play an important role in making foreign policies that have an impact on the security stability of the Republic of Korea.